833 Hyper Acute Dialysis Access Pathway (HADAP) – Undertaking Creation of Arteriovenous Fistulae in The Renal Ward. (4th May 2021) - Shetty, S; Chowdary, P; Dabare, D; Seet, C; Ahmed, R; Barlas, A; Lindsey, B
Abstract: Introduction: The impetus to apply the "lean method" to creation of arteriovenous fistulae came with the pandemic restricting access to theatres. Here we present HADAP implemented in a dedicated procedure room in the Renal ward. Method: : Between April and September 2020, 44 patients underwent ward-based arteriovenous fistula operations with no more than 3 people in the room – surgeon, runner and patient. The parameters assessed were duration of operation, complications, patency, patient and surgeon feedback and financial implications. Results: : The service was predominantly registrar-led who created 91% of the fistulae. 95% operations were completed successfully with a 2-week primary patency of 73% and no surgical site infections. 40% of the procedures were radiocephalic fistulae. 14% procedures required surgical assistance by the runner. The average operating time reduced from 90 minutes for the first 10 cases to 50 minutes for the last 9. A structured questionnaire showed positive feedback from both patients and surgeons (4-5 out of 5). This service has cleared potentially 9 main theatre lists for more complex procedures. Conclusions: : Our study demonstrates the successful implementation of a novel operating environment allowing expedited care for renal failure patients. It has enhanced our ability to deliver a dialysis access program despite the challenges of COVID.